Jury member for the selection of the Best Student Animation Category in VAF 2019 - Margaritis, Charalambos (My University, 2026)
Selection of the films to be awarded the Best Student Animation Award of the 2019 edition of the Viborg Animation Festival, organized by The Animation Workshop (VIA University College) in Denmark.